A Canadian, retrospective, multicenter experience with selexipag for a heterogeneous group of pediatric pulmonary hypertension patients - Youssef, David; Richards, Susan; Lague, Sabine; Sheppard, Catherine; Smith, Jenna; Vorhies, Erika; Hosking, Martin; Pietrosanu, Matthew; Bates, Angela (Frontiers in Pediatrics, 2023)
Introduction: Selexipag, an oral nonprostanoid prostaglandin receptor agonist, has led to reduced morbidity and mortality in adults with pulmonary arterial hypertension (PAH). While the adult literature has been extrapolated to suggest selexipag as an oral treatment for severe pediatric pulmonary hypertension (PH), longitudinal, multicenter data on the benefits of selexipag in this population are lacking. The purpose of this study is to present a longitudinal, multicentre experience with selexipag in a relatively large cohort of pediatric PH patients and add to the existing selexipag literature.